2019
DOI: 10.1371/journal.pone.0224016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of intraoperative hyperlactatemia during craniotomy

Abstract: ObjectPatients often develop markedly elevated serum lactate levels during craniotomy although the reason for this is not entirely understood. Elevated lactate levels have been associated with poor outcomes in critically ill septic shock patients, as well as patients undergoing abdominal and cardiac surgeries. We investigated whether elevated lactate in craniotomy patients is associated with neurologic complications (new neurological deficits) as well as systemic complications.MethodsWe performed a cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…15 This study showed that hyperlactatemia lengthens hospital stay. The results in the literature generally confirm this 16,17 unlike Lawton et al 18 This presented study had some strengths. Repeat lactate measurements were used instead of a single blood sample.…”
Section: Discussionsupporting
confidence: 68%
“…15 This study showed that hyperlactatemia lengthens hospital stay. The results in the literature generally confirm this 16,17 unlike Lawton et al 18 This presented study had some strengths. Repeat lactate measurements were used instead of a single blood sample.…”
Section: Discussionsupporting
confidence: 68%
“…In the literature, studies are showing that there is a relationship between high lactate levels and prolonged stay in the hospital. 18,23 Some studies do not display this result. 13 In our study, the duration of hospitalization was significantly extended in patients with perioperative persistent lactate height.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, the influence of the intraoperative status could not be assessed. Several studies have evaluated mortality or other postoperative complications associated with elevated lactate levels in various surgeries [ 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but the association has never been evaluated specifically between intraoperative lactate levels and MINS, which share a common mechanism-related oxygen demand and supply mismatch. We demonstrated that patients with intraoperative hyperlactatemia had an increased risk of MINS.…”
Section: Discussionmentioning
confidence: 99%